The Self-Concept of Adolescent Girls Regarding Physical Changes During Puberty - Kartikasari, Ratih Indah; Primindari, Risya Secha; Nurafifah, Dian; Kusumaningrum, Andri Tri; Mauliyah, Ihda (Universitas Muhammadiyah Lamongan, 2023)
Introduction: Self-conception is a mental health problem often experienced by teenage girls who will or have experienced menstruation, especially during early puberty. This situation requires special attention. According to a preliminary survey conducted by the researchers of the State Primary School 1 Turi District of Lamongan, 80% of teenagers have experienced physical changes. The aim of this study was to determine the description of a teenage girl's self-concept about physical changes during puberty.Methods: descriptive research design. The research population was part of the seventh grade teenage children in the State 1 Turi High School, Turi district, Lamongan district, with a sample size of 40 teenage girls. Sampling is done using quota sampling. Data collection method with closed questionnaires. The data collected is analyzed descriptively.Results: 92.5% of adolescents have a negative self-image. 77.5% have negative ideas about themselves, and 90% of teenagers have bad self-esteem.Conclusion: Almost all of the teenage girls in the 7th grade in the 1st grade in Turi, Turi district, and Lamongan district have a negative self-concept. Counseling teachers and UKS (School Health Unit) should work together to provide communication, information, and education on physical changes in adolescents during puberty, especially women's gymnastics, so that they have a positive self-concept and adolescent girls' mental health is improved. Keywords: self-concept, puberty, physical change, female adolescence